Implementation of Research Results as Collaboration with Stakeholders in the Era of the COVID-19 Pandemic - Wibisiono, Aryo Bayu; Nisa, Diana Aqidatun; Izza, Navisatul; Putra, Agung Brastama (ADBE, 2021)
Research is an essential part of education for Lecturers or Teachers. Research schemes usually refer to results used by the public, or theoretically based research, to support the novelty of other research. In a research model with output results, the current pandemic will significantly impact the community’s applied research. Utilizing research results in collaboration with stakeholders will provide benchmarks and collaboration between lecturers and the industrial world. This research is derived from previous research with the theme of the folklore "Sarip Tambak Oso." This research is a descriptive research model that can be developed into further research. The data collection methods in this research are in-depth interviews and product manufacturing tests by the industry. To collect data regularly, this research will involve stakeholders of PT GRD Indonesia based on creative industries as research partners.